Misja Piotra Parczewicza do Kozaków w 1657 r. - Milewski, Dariusz (Saeculum Christianum. Pismo Historyczne, 2019)
The article analyses the mission of the archbishop of Marcianopolis Petar Parchevich, who, at the beginning of 1657, went to Bohdan Khmelnytsky. He was commissioned by Emperor Ferdinand III and intended to bring about Polish-Cossack reconciliation. Its aim was to enable Poland to effectively fight the Swedes. The messenger himself hoped to involve the Cossacks in the war with Turkey. Unfortunately, the mission did not bring the expected results.